Neoskrjabinotaenia sindensis Gen.N. Sp.N. (Cestoda Catenotaeniidae) from Tetra indica - Bilqees, Fatima Mujib (1982)
A study was made on the parasites found in specimens of tetra indica, a rodent colleted from certain areas of sind cestodes were recovered, together with other helminths, which on closer examination were found to belong to an undescribed genus of the family catenotaeniidae Spassky (1950). Upon further studies on their characteristics, a new genus neoskrjabinotaenia and species sindensis were established to distinguish these cestodes from the others.
Includes bibliographical references (page 187) and index.
Keywords: Zoology; Catenotaeniidae -- Classification; Sesbania grandiflora -- Pharmacology; Tetra indica -- Description